2007
DOI: 10.1079/pavsnnr20072060
|View full text |Cite
|
Sign up to set email alerts
|

Bt corn and impact on mycotoxins.

Abstract: This review summarizes the literature linking Bt [Bacillus thuringiensis] corn and the reduction of the mycotoxins fumonisin, aflatoxin, deoxynivalenol (DON) and zearalenone. Mycotoxins in field corn cause hundreds of millions of dollars in economic losses annually in the USA, and substantially greater losses in other regions of the world. Most of the losses are from aflatoxin contamination, while significant but smaller losses are due to Fusarium mycotoxins, fumonisins and DON. The insecticidal proteins in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…The authors concluded that, according to EU regulation, 93% of the Bt maize crops could be sold as food/feed, compared with only 45% for conventional maize. A significant reduction in certain mycotoxins in Bt maize compared with conventional maize has also been reported from other experimental studies across European countries and the United States 13, 39. Furthermore, reduced silk clipping and kernel feeding by corn borer larvae and corn rootworm adults is particularly beneficial in seed and sweet maize production, where high grain quality is essential for marketing 15…”
Section: Incentives To Growing Bt Maizesupporting
confidence: 53%
“…The authors concluded that, according to EU regulation, 93% of the Bt maize crops could be sold as food/feed, compared with only 45% for conventional maize. A significant reduction in certain mycotoxins in Bt maize compared with conventional maize has also been reported from other experimental studies across European countries and the United States 13, 39. Furthermore, reduced silk clipping and kernel feeding by corn borer larvae and corn rootworm adults is particularly beneficial in seed and sweet maize production, where high grain quality is essential for marketing 15…”
Section: Incentives To Growing Bt Maizesupporting
confidence: 53%
“…If texture (endosperm type) had a major effect on mycotoxin accumulation, H614 would have been the most resistant variety, but it was the most contaminated of the varieties we investigated. Insect damage has previously been associated with mycotoxin contamination (Hell et al 2000;Wu 2007). However, we did not find a correlation between mycotoxins and weevils.…”
Section: Discussionmentioning
confidence: 99%
“…In areas with high infestation of the European and Mediterranean corn borer, claimed benefits of Bt-maize are (i) higher yield levels compared with non-GM maize varieties; (ii) less pesticide treatments; (iii) lower pest damage, resulting in decreased levels of mycotoxins (e.g., fumonisin); and therefore (iv) enhanced safety and quality for animal and human consumption Wu, 2006Wu, , 2007Gómez-Barbero et al, 2008). Proponents even argue that greater efficiency, productivity and management flexibility would enhance economic competitiveness.…”
Section: Proponents' Rationale On Coexistencementioning
confidence: 99%